Fostering Research Motivation for Students Through Learning Development with A Research-Based Flipped Classroom Model - Kamal, Muhiddinur; Shafra, Shafra; Rahmiati, Rahmiati; Sulong, Abdul Ramae; Arriafdi, Muhammad Zainuddin bin; Aprison, Wedra; Kher, Dinovia Fannil (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to foster research from an early age by developing the Research Based Flipped Classroom (RBFC) Learning model at Islamic High School. The method used was Research and Development (RnD) to produce specific products and test the effectiveness of these products by adapting the McKenny Model as a stage consisting of preliminary research, prototyping phase, and assessment stage. Through preliminary studies in the form of content analysis and literature studies, the activities carried out are to analyze the objectives within the limitations of the material developed, design learning, and test the validity, effectiveness and practicality of the designed model. The results of this study 1). The development of the Research-Based Flipped Classroom (RBFC) learning model has been proven to significantly improve student learning outcomes at MA Sjech Ibrahim-Koto Tuo- Pasaman; 2). This Research-Based Flipped Classroom (RBFC) learning model can be declared valid after being validated by the validator; and 3). There is a practical level of practical application of the Research-Based Flipped Classroom (RBFC) Learning model, with evidence of its development and increasing student creativity in learning. Thus, applying the Research-Based Flipped Classroom (RBFC) learning model can develop research literacy early and be an alternative in selecting learning models used in Madrasah Aliyah.